A Comparative Investigation into Training Intensity Distribution for Elite Athletes: Systematic Review (International Journal of Physiotherapy, 2025)
Background: Endurance sports demand a finely-tuned balance between training intensity and volume to optimize athletic performance. Training Intensity Distribution has become a critical training parameter in endurance sports, potentially eliciting superior physiological adaptations and improving overall performance outcomes. Training intensity distribution influences the body's aerobic and anaerobic energy systems, enhancing endurance performance. So, the study aims to explore the best training intensity distribution for elite athletes.Methods: We searched three electronic databases for original research articles. After analyzing the resultant original articles, studies were included if they met the following criteria: a) participants were endurance sport athletes; b) studies analyzed training intensity distribution in the form of interventions only; c) studies were published in peer-reviewed journals and d) studies analyzed training programs with a duration of 4 weeks or longer. The selected studies were then assessed using the PEDro scale.Results: During the search of the three electronic databases, we found 10 articles. Six favored polarized training, whereas one favored pyramidal training. Two showed that low-intensity dominant training is better, and one said that a transition from pyramidal to polarized training as the competition approaches is better. The mean PEDro scale rating is 4.9.Conclusion: Based on the research, both pyramidal and polarized training intensity distributions have merits and can be effective in different contexts. Ultimately, the choice between pyramidal and polarized training intensity distribution should consider individual athlete characteristics, sport-specific requirements, training phase, and other contextual factors.